Impacto económico de la aplicación de la Ley Orgánica de la Economía Popular y Solidaria y del Sector Financiero Popular y Solidario en el ámbito microfinanciero del cantón Salcedo durante el año 2012. - Torres López, Sixto Marcelo (2014)
Through history the credit for small business that has driven the economy of a region and that is why governments have been concerned that regulate and streamline this concept. As the current governments concerns want to do this by creating a law to be responsible for the financial part, and besides strengthen entrepreneurship of small business, this has required financial institutions they are fast and efficient small loan to fit the situational parameters of society. The limited information that exists in documents makes many people do not know anything the consequences of law enforcement, advantages and disadvantages, consequences and requirements, is why it first analyzes the present structure of the financial system, guidance that the government wants to give through the application of the ‘Ley Orgánica de la Economía Popular y Solidaria’; and finally, study results presented made to small entrepreneurs of Salcedo, that with hard work and tenacity have significantly enhanced leverage this sector for rulers and ruled align efforts for mutual benefit.